Effect Of Methyl Mercury towards Number of Microglia Cells and Expression of iNOS On The Brain in Rats (Rattus norvegicus) - Yuli Kusuma Dewi; Aulanni'am Aulanni'am; Chanif Mahdi (Chemistry Department, The University of Brawijaya, 2014)
Methyl mercury (MeHg) has the highest toxicity among the derivative of the organic mercury compounds. Rate of accumulation of MeHg in the body is very high because it is soluble in lipids. The ability of methyl mercury binds to proteins in the body causing MeHg to penetrate the blood-brain barrier easily, so that it can quickly disrupt the central nervous system and speed up nerve cell damage. This paper reported the effect of methyl mercury on the number of microglia cells and expression of iNOS in the brains of Rattus norvegicus. In this study, rats were divided into two groups: a control group with no exposure of MeHg and groups of rats exposed with MeHg at a dose of 0.6 mg/kg BW/day given orally for 21 days. Number of microglia cells is investigated using silver nitrate staining method and iNOS expression is determined by immunohistochemistry methods. The results showed that exposure with MeHg in a dose of 0.6 mg/kgBW can increase the number of microglia cells and iNOS expression respectively as mush as 151.63% and 918.08% . Keyword: Methyl mercury, microglia, brain, iNOS, immunohistochemistry